The Methods of Promoting Food Culture among Kindergarten Children A Field Study on a Sample of Kindergarten Teachers in Tartous City - سحر الراعي (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research aimed to identify the practices of the kindergarten teacher while the children eat the meal, and to identify the role of the kindergarten teacher in promoting healthy food awareness among children in the kindergartens of Tartous city. In order to achieve the objectives of the research, the questionnaire prepared for this purpose was applied, consisting of (44) phrases, which included two axes (the first axis is the kindergarten teacher's practices while children eat the meal, and the second axis is the kindergarten teacher's role in promoting healthy food awareness among children), the descriptive approach was used The questionnaire was applied to a sample consisting of (144) kindergarten teachers in the kindergartens of Tartous City during the academic year 2022/2023 The research results showed that the teacher's practices while the children ate the meal came to a middle degree, and the teacher's role in promoting healthy food awareness among kindergarten children in the city of Tartous came to a middle degree. The research presented several recommendations, the most important of which are: Raising the efficiency of kindergarten teachers through the establishment of training and educational courses that contribute to activating the concepts of food culture for kindergarten children, and introducing various educational activities and awareness programs in kindergartens that contribute to educating kindergarten children in the nutritional aspect.